2013
DOI: 10.1111/jcpp.12068
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anxiety symptoms in a large‐scale twin study of children with autism spectrum disorders, their co‐twins and controls

Abstract: These findings support previous reports of heightened anxiety in children with ASDs, at least on parent-reported measures. Unaffected co-twins of children with ASDs also showed increased anxiety, generating questions about the potential etiological overlap between ASDs and anxiety. Progress in this area now depends on more refined anxiety measurement in ASDs and continued investigation of interrater differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 41 publications
6
52
0
Order By: Relevance
“…These results are in line with Schwartz et al's (2009) study where parents described their children with ASD as having a temperament comprising more negative affectivity and fear, and less pleasure. More broadly, our results fit well with a growing number of studies on negative affectivity in ASD (Hallett et al 2013) frequently highlighting comorbid anxiety and depression disorders (Hofvander et al 2009;Lugnegård et al 2011;Sterling et al 2008;Stewart et al 2006). Depression and anxiety are even considered as secondary disorders in ASD (Schultz 2005), and the impact of psychopharmacological interventions targeting anxiety and mood disorders in individuals with ASD is now being developed (Boyd et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…These results are in line with Schwartz et al's (2009) study where parents described their children with ASD as having a temperament comprising more negative affectivity and fear, and less pleasure. More broadly, our results fit well with a growing number of studies on negative affectivity in ASD (Hallett et al 2013) frequently highlighting comorbid anxiety and depression disorders (Hofvander et al 2009;Lugnegård et al 2011;Sterling et al 2008;Stewart et al 2006). Depression and anxiety are even considered as secondary disorders in ASD (Schultz 2005), and the impact of psychopharmacological interventions targeting anxiety and mood disorders in individuals with ASD is now being developed (Boyd et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…SC ability is a continuously distributed trait that extends throughout the general population, 9 with those who experience severe difficulties often receiving a diagnosis of autism spectrum disorder (ASD), a neurodevelopmental condition characterized by SC difficulties and restricted interests and repetitive behaviors. SA co-occurs highly in children with ASD (4.5−9.5 years) and high subthreshold ASD traits (10−15 years),10, 11 suggesting that those with greater SC difficulties may have a heightened risk of developing SA disorder. However, the developmental relationship between SC difficulties and SA is unclear.…”
Section: Sa and Social Communication Difficulties In Childhoodmentioning
confidence: 99%
“…Kerns et al [12▪] found that language ability was associated with traditional DSM-defined anxiety, whereas ASD severity was associated with atypical anxiety. Additionally, Hallett et al [14▪] found differential relationships between particular types of anxiety and ASD symptoms. Social anxiety was negatively correlated with social and communication impairment, whereas panic and OCD symptoms were positively correlated with the restricted and repetitive behaviors (RRBs).…”
Section: Prevalence and Phenotype Of Anxiety In Autism Spectrum Disordermentioning
confidence: 99%
“…In a study of older children with ASD, higher verbal IQ was associated with greater anxiety, but nonverbal IQ was unrelated [9▪]. Regarding specific types of anxiety, Hallett et al [14▪] found that social anxiety was positively correlated with IQ, whereas separation anxiety was negatively correlated with IQ. These results highlight the differential impact of cognitive and verbal ability on the experience and behavioral manifestations of anxiety among children with ASD.…”
Section: Risk Factors and Correlates Of Anxiety In Autism Spectrum DImentioning
confidence: 99%